Limitación del libre desarrollo de la personalidad del cónyuge, ante la inexistencia del divorcio incausado en nuestra legislación - Flores Morquecho, Bilmania Teresa (2023)
This research work addressed a contemporary issue of the institution of divorce which, anchored in the social transformations and universal evolutions of human rights, require new guidelines in the Ecuadorian infra-constitutional order. In a critical and well- founded way, it seeks to leave behind the causal divorce and the incorporation of uncaused divorce is proposed as a legal figure which guarantees the promotion of the right of free development of individual personality, protected in the Republic of Ecuador’s constitution, that promote the freedom and self-determination of the person in front of their life projects. The methodology was on a descriptive, non-experimental and cross-sectional level, part of a mixed approach (qualitative-quantitative), inductive-deductive, historical-logical, analytical- synthetic, corporate and dogmatic methods were used; as well as techniques of bibliographic review, signing, documentary review, a survey to the judges and lawer of the Calvas canton and an interview to an expert in constitutional law. As a result, it was justified that the causal system used in divorce proceedings under current regulations is regressive and violates constitutional individual rights. Finally, a reform to our Ecuadorian legislation is proposed, which allows the correct development of self-protection of the individual, as established in the Constitution.